Lithium metal negative electrode and preparation method and application thereof

By spraying PTCDA solution on the surface of the lithium sheet of the lithium ion battery and adding PTCDA to the solid electrolyte, an integrated electrolyte-negative electrode structure is formed, and the safety and dynamic performance problems of the lithium ion battery are solved, achieving higher safety performance and Cyclic performance.

CN119419391AInactive Publication Date: 2025-02-11帕瓦(诸暨)固态钠能有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510012991.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have safety problems such as thermal runaway, combustion, and explosion, and the solid electrolytes of all-solid-state lithium-ion batteries have poor contact and low ionic conductivity, which affects their kinetic performance.

Method used

通过将PTCDA和第一锂盐与溶剂混合,制得溶液A,并喷涂于锂片表面,形成活化面;同时,添加PTCDA至固态电解质中,提高其离子电导率,并与锂金属负极组合,形成电解质-负极一体化结构。

Benefits of technology

The interface contact performance between solid electrolyte and lithium sheet is improved, the safety performance of the battery is enhanced, and the dynamic performance and cycling performance of the battery are improved by improving the lithium ion conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419391A_ABST
    Figure CN119419391A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery materials, and discloses a lithium metal negative electrode and a preparation method and application thereof, and the preparation method of the lithium metal negative electrode comprises the following steps: mixing a first lithium salt, PTCDA (3, 4, 9, 10-perylenetetracarboxylic dianhydride) and a first solvent to prepare a solution A, spraying the solution A on one side surface of a lithium sheet, and drying to obtain the lithium metal negative electrode. The PTCDA and the first lithium salt are used for modifying the lithium sheet of the lithium battery, an SEI film can be generated on the surface of the lithium sheet, the interface contact performance of the solid electrolyte and the lithium sheet can be improved, and the safety performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery materials and relates to the preparation of lithium ion battery materials, in particular to a lithium metal negative electrode and a preparation method thereof, an electrolyte-negative electrode integrated structure and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are popular in the market due to their high energy density and long cycle life. However, with the development of liquid lithium-ion batteries, problems such as thermal runaway, combustion, and explosion have gradually affected the development of lithium-ion batteries. Therefore, the development of lithium-ion batteries with high safety is an urgent problem to be solved.

[0003] All-solid-state lithium-ion batteries have extremely high safety compared to liquid lithium-ion batteries because they do not have liquid phase components with high saturated vapor pressure and the flame retardant properties of the material itself. However, solid electrolytes have poor contact with lithium sheets because they do not have fluidity and even have a certain degree of rigidity. In addition, the ionic conductivity inside the solid electrolyte also needs to be further improved to reduce polarization and increase kinetic performance. Summary of the invention

[0004] In view of the above problems existing in the prior art, in the first aspect, the present invention provides a method for preparing a lithium metal negative electrode; in the second aspect, the present invention provides a lithium metal negative electrode; in the third aspect, the present invention provides a method for preparing an electrolyte-negative electrode integrated structure; in the fourth aspect, the present invention provides an electrolyte-negative electrode integrated structure; in the fifth aspect, the present invention provides a battery.

[0005] In a first aspect, the present invention provides a method for preparing a lithium metal negative electrode, comprising: mixing a first lithium salt, PTCDA (3,4,9,10-perylenetetracarboxylic dianhydride) and a first solvent to prepare a solution A, spraying the solution A on one side of a lithium sheet and then drying; the side of the lithium sheet sprayed with the solution A is an activated surface.

[0006] Preferably, the first lithium salt is one or more of LiFSI (lithium bis(fluorosulfonyl)imide), LiNO3 (lithium nitrate), and LiPF6 (lithium hexafluorophosphate).

[0007] Preferably, the first solvent is one or both of THF (tetrahydrofuran) and NMP (N-methylpyrrolidone).

[0008] Preferably, in solution A, the concentration of lithium salt is 0.01-0.03 mol / L; the concentration of PTCDA is 1.1-3.3 g / L.

[0009] Preferably, the spraying amount of solution A on the lithium battery lithium sheet is 2-5 μL / cm 2 .

[0010] In a second aspect, the present invention provides a lithium metal negative electrode prepared by the above preparation method.

[0011] In a third aspect, the present invention provides an electrolyte-negative electrode integrated structure, comprising a solid electrolyte and a lithium metal negative electrode prepared by the above preparation method or the above lithium metal negative electrode, wherein the active surface of the lithium sheet is bonded to the solid electrolyte.

[0012] In a fourth aspect, the present invention provides a method for preparing the above-mentioned electrolyte-negative electrode integrated structure, comprising: contacting the active surface of the lithium sheet with the solid electrolyte, and pressing the lithium metal negative electrode and the solid electrolyte under a certain pressure.

[0013] Preferably, when preparing the solid electrolyte, the second lithium salt, the polymer, PTCDA and the second solvent are mixed to obtain a solution B, and the solution B is coated on the substrate and dried.

[0014] Preferably, the second lithium salt is one or more of LiFSI (lithium bis(fluorosulfonyl)imide), LiNO3 (lithium nitrate), and LiPF6 (lithium hexafluorophosphate).

[0015] Preferably, the polymer is one or more of PVDF (polyvinylidene fluoride), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), and PVDF-CTFE (polyvinylidene fluoride-chlorotrifluoroethylene copolymer).

[0016] Preferably, the second solvent is any one or both of DMF (N,N-dimethylformamide) and THF (tetrahydrofuran).

[0017] Preferably, in solution B, the concentration of the second lithium salt is 0.3-0.7 mol / L; the concentration of the polymer is 80-130 g / L; and the concentration of PTCDA is 0.8-3.9 g / L.

[0018] Preferably, during drying, the mixture is first dried at room temperature for 24 hours and then transferred to an oven and dried at 90° C. for 2 hours.

[0019] Preferably, when the lithium metal anode and the solid electrolyte are pressed together, the pressure is 5-12 N / cm 2 , the pressing time is 0.5-1.5h.

[0020] In a fifth aspect, the present invention provides a battery comprising the above-mentioned electrolyte-negative electrode integrated structure or the electrolyte-negative electrode integrated structure prepared by the above-mentioned preparation method.

[0021] Compared with the prior art, one or more technical solutions provided by the present invention have at least one of the following beneficial technical effects: (1) Using PTCDA to modify the lithium sheet of lithium battery can generate SEI film on the surface of lithium sheet, which can improve the interface contact performance between solid electrolyte and lithium sheet, and is beneficial to improve the safety performance of battery.

[0022] (2) Adding PTCDA to the solid electrolyte makes the solid electrolyte have higher ionic conductivity, which can improve the lithium ion conductivity when combined with the lithium metal negative electrode.

[0023] (3) The preparation process of the electrolyte-negative electrode integrated structure provided by the present invention is simple, the production conditions are green and clean, and there is no need to recycle waste gas or waste liquid, which is conducive to promotion and marketization. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The cycle performance diagram of the battery assembled with the electrolyte-negative electrode integrated structure prepared in Example 1 and Comparative Examples 1-2; Figure 2 The cycle performance diagram of the battery assembled with the electrolyte-negative electrode integrated structure prepared in Examples 3 to 5. DETAILED DESCRIPTION

[0025] The present invention provides the following specific technical solutions.

[0026] In a first aspect, the present invention provides a method for preparing a lithium metal negative electrode, comprising: mixing a first lithium salt, PTCDA (3,4,9,10-perylenetetracarboxylic dianhydride) and a first solvent to prepare a solution A, spraying the solution A on one side of a lithium sheet and then drying; the side of the lithium sheet sprayed with the solution A is an activated surface.

[0027] Research has found that PTCDA (3,4,9,10-tetracarboxylic anhydride) can react spontaneously with lithium metal. By spraying a certain concentration of PTCDA on the surface of lithium battery lithium sheets and reacting for a certain period of time, an artificial SEI film is generated, which can enhance the contact between the solid electrolyte and the lithium sheet interface and help improve the safety performance of the battery.

[0028] Preferably, the first lithium salt is one or more of LiFSI (lithium bis(fluorosulfonyl)imide), LiNO3 (lithium nitrate), and LiPF6 (lithium hexafluorophosphate).

[0029] Preferably, the first solvent is one or both of THF (tetrahydrofuran) and NMP (N-methylpyrrolidone).

[0030] Preferably, in solution A, the concentration of lithium salt is 0.01-0.03 mol / L; the concentration of PTCDA is 1.1-3.3 g / L.

[0031] Preferably, the spraying amount of solution A on the lithium battery lithium sheet is 2-5 μL / cm 2.

[0032] In practical applications, the concentration of the first lithium salt, the concentration of PTCDA, and the spraying amount of solution A on the lithium battery lithium sheet can be adjusted according to actual conditions, and the above ranges are only preferred ranges obtained through multiple experiments.

[0033] In a second aspect, the present invention provides a lithium metal negative electrode prepared by the above preparation method.

[0034] In a third aspect, the present invention provides an electrolyte-negative electrode integrated structure, comprising a solid electrolyte and a lithium metal negative electrode prepared by the above preparation method or the above lithium metal negative electrode, wherein the active surface of the lithium sheet is bonded to the solid electrolyte.

[0035] In a fourth aspect, the present invention provides a method for preparing the above-mentioned electrolyte-negative electrode integrated structure, comprising: contacting the active surface of the lithium sheet with the solid electrolyte, and pressing the lithium metal negative electrode and the solid electrolyte under a certain pressure.

[0036] Research has found that the PTCDA molecule has a certain π bond structure and has four sites that can bind to lithium ions. Adding it to the solid electrolyte can make the solid electrolyte have a higher ion conductivity. The solid electrolyte added with PTCDA can be combined with a lithium metal negative electrode to reduce the probability of side reactions caused by direct contact between lithium metal and the electrolyte on the one hand; on the other hand, it can increase the lithium ion transmission channel inside the solid electrolyte, improve lithium ion conductivity, and reduce interface impedance. In addition, the preparation method proposed in the present invention is simple, and the production conditions are green and clean, which is conducive to promotion and marketization.

[0037] Preferably, when preparing the solid electrolyte, the second lithium salt, the polymer, PTCDA and the second solvent are mixed to obtain a solution B, and the solution B is coated on the substrate and dried.

[0038] Preferably, the second lithium salt is one or more of LiFSI (lithium bis(fluorosulfonyl)imide), LiNO3 (lithium nitrate), and LiPF6 (lithium hexafluorophosphate).

[0039] Preferably, the polymer is one or more of PVDF (polyvinylidene fluoride), PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene), and PVDF-CTFE (polyvinylidene fluoride-chlorotrifluoroethylene copolymer).

[0040] Preferably, the second solvent is any one or both of DMF (N,N-dimethylformamide) and THF (tetrahydrofuran).

[0041] Preferably, in solution B, the concentration of the second lithium salt is 0.3-0.7 mol / L; the concentration of the polymer is 80-130 g / L; and the concentration of PTCDA is 0.8-3.9 g / L.

[0042] Preferably, during drying, the mixture is first dried at room temperature for 24 hours and then transferred to an oven and dried at 90° C. for 2 hours.

[0043] Preferably, when the lithium metal anode and the solid electrolyte are pressed together, the pressure is 5-12 N / cm 2 , the pressing time is 0.5-1.5h.

[0044] In practical applications, the concentration of the second lithium salt, the concentration of the polymer, the drying process, the pressing pressure and the pressing time can be adjusted according to actual conditions. The above ranges and drying process are the preferred ranges obtained after multiple experiments.

[0045] In a fifth aspect, the present invention provides a battery comprising the above-mentioned electrolyte-negative electrode integrated structure or the electrolyte-negative electrode integrated structure prepared by the above-mentioned preparation method.

[0046] In order to make the technical problems to be solved, technical solutions and technical advantages of the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0047] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0048] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0049] Embodiment 1: A method for preparing an electrolyte-negative electrode integrated structure comprises the following steps: (1) Take 3.74g LiFSI and 1.5g PTCDA and add them to 1L THF solvent, and stir them thoroughly to dissolve and disperse them to obtain solution A. In a glove box with an oxygen content of less than 0.01ppm and a water content of less than 0.01ppm, take 100μL of solution A and spray it evenly on one side of a 5cm*5cm lithium foil. After standing for 7h, a lithium metal negative electrode is obtained. The side of the lithium foil sprayed with solution A is the activated side. (2) Take 93.53g LiFSI, 100g PVDF-HFP, and 1.5g PTCDA and dissolve them in 1L DMF. Mix and dissolve them thoroughly to obtain solution B. Use a 500μm scraper to evenly coat solution B on a glass plate with a coating thickness of 150μm. Then let the glass plate stand and dry at room temperature for 24h, and then transfer it to a 90℃ forced air oven and dry it for 2h to obtain a solid electrolyte. (3) Lay the activated surface of the lithium sheet prepared in step (1) on the solid electrolyte prepared in step (2) at 10 N / cm 2 The electrolyte-negative electrode integrated structure was obtained by pressing under a pressure of 1 h.

[0050] Comparative Example 1: A method for preparing an electrolyte-negative electrode integrated structure comprises the following steps: (1) Take a 5cm*5cm lithium foil; (2) Take 93.53g LiFSI, 100g PVDF-HFP, and 1.5g PTCDA and dissolve them in 1L DMF. Mix and dissolve them thoroughly to obtain solution B. Use a 500μm scraper to evenly coat solution B on a glass plate with a coating thickness of 150μm. Then let the glass plate stand and dry at room temperature for 24h, and then transfer it to a 90℃ forced air oven and dry it for 2h to obtain a solid electrolyte. (3) Lay the lithium foil prepared in step (1) on the solid electrolyte prepared in step (2) at 10 N / cm 2 The electrolyte-negative electrode integrated structure was obtained by pressing under a pressure of 1 h.

[0051] Comparative Example 2: A method for preparing an electrolyte-negative electrode integrated structure comprises the following steps: (1) Take a 5cm*5cm lithium foil; (2) Take 93.53g LiFSI and 100g PVDF-HFP and dissolve them in 1L DMF, mix and dissolve them thoroughly to obtain solution B, use a 500μm scraper to evenly coat solution B on a glass plate with a coating thickness of 150μm, then let the glass plate stand and dry at room temperature for 24h, and then transfer it to a 90℃ forced air oven and dry it for 2h to obtain a solid electrolyte; (3) Lay the lithium foil prepared in step (1) on the solid electrolyte prepared in step (2) at 10 N / cm 2 The electrolyte-negative electrode integrated structure was obtained by pressing under a pressure of 1 h.

[0052] Embodiment 2: (1) Take 3.74g LiFSI and 1.5g PTCDA and add them to 1L THF solvent, and stir them thoroughly to dissolve and disperse them to obtain solution A. In a glove box with an oxygen content of less than 0.01ppm and a water content of less than 0.01ppm, take 100μL of solution A and spray it evenly on one side of a 5cm*5cm lithium foil. After standing for 7h, a lithium metal negative electrode is obtained. The side of the lithium foil sprayed with solution A is the activated side. (2) Take 93.53g LiFSI and 100g PVDF-HFP and dissolve them in 1L DMF, mix and dissolve them thoroughly to obtain solution B, use a 500μm scraper to evenly coat solution B on a glass plate with a coating thickness of 150μm, then let the glass plate stand and dry at room temperature for 24h, and then transfer it to a 90℃ forced air oven and dry it for 2h to obtain a solid electrolyte; (3) Lay the activated surface of the lithium sheet prepared in step (1) on the solid electrolyte prepared in step (2) at 10 N / cm 2 The electrolyte-negative electrode integrated structure was obtained by pressing under a pressure of 1 h.

[0053] Embodiment 3: (1) Take 6.7g LiNO3 and 1.1g PTCDA and add them to 1L NMP solvent, and stir them thoroughly to dissolve and disperse them to obtain solution A. In a glove box with an oxygen content of less than 0.01ppm and a water content of less than 0.01ppm, take 50μL of solution A and spray it evenly on one side of a 5cm*5cm lithium foil. After standing for 7h, a lithium metal negative electrode is obtained. The side of the lithium foil sprayed with solution A is the activated side. (2) Take 4.56g LiPF6, 80g PVDF-HFP, and 0.8g PTCDA and dissolve them in 1L DMF. Mix and dissolve them thoroughly to obtain solution B. Use a 500μm scraper to evenly coat solution B on a glass plate with a coating thickness of 150μm. Then let the glass plate stand and dry at room temperature for 24h, and then transfer it to a 90℃ forced air oven and dry it for 2h to obtain a solid electrolyte. (3) Lay the activated surface of the lithium sheet prepared in step (1) on the solid electrolyte prepared in step (2) at 5 N / cm 2 The electrolyte-negative electrode integrated structure was obtained by pressing under a pressure of 0.5 h.

[0054] Embodiment 4: (1) Take 20g LiPF6 and 3.3g PTCDA and add them to 1L NMP solvent, and stir them thoroughly to dissolve and disperse them to obtain solution A. In a glove box with an oxygen content of less than 0.01ppm and a water content of less than 0.01ppm, take 125μL of solution A and spray it evenly on one side of a 5cm*5cm lithium foil. After standing for 7h, a lithium metal negative electrode is obtained. The side of the lithium foil sprayed with solution A is the activated side. (2) Take 10.64g LiPF6, 130g PVDF-HFP, and 3.9g PTCDA and dissolve them in 1L DMF. Mix and dissolve them thoroughly to obtain solution B. Use a 500μm scraper to evenly coat solution B on a glass plate with a coating thickness of 150μm. Then let the glass plate stand and dry at room temperature for 24h, and then transfer it to a 90℃ forced air oven and dry it for 2h to obtain a solid electrolyte. (3) Lay the activated surface of the lithium sheet prepared in step (1) on the solid electrolyte prepared in step (2) at 12 N / cm 2 The electrolyte-negative electrode integrated structure was obtained by pressing under a pressure of 1.5 h.

[0055] Embodiment 5: (1) Take 10g LiPF6 and 2g PTCDA and add them to 1L NMP solvent, and stir them thoroughly to dissolve and disperse them to obtain solution A. In a glove box with an oxygen content of less than 0.01ppm and a water content of less than 0.01ppm, take 100μL of solution A and spray it evenly on one side of a 5cm*5cm lithium foil. After standing for 7h, a lithium metal negative electrode is obtained. The side of the lithium foil sprayed with solution A is the activated side. (2) Take 5g LiPF6, 100g PVDF-HFP, and 2g PTCDA and dissolve them in 1L DMF. Mix and dissolve them thoroughly to obtain solution B. Use a 500μm scraper to evenly coat solution B on a glass plate with a coating thickness of 150μm. Then let the glass plate stand and dry at room temperature for 24h, and then transfer it to a 90℃ forced air oven and dry it for 2h to obtain a solid electrolyte. (3) Lay the activated surface of the lithium sheet prepared in step (1) on the solid electrolyte prepared in step (2) at 10 N / cm 2 The electrolyte-negative electrode integrated structure was obtained by pressing under a pressure of 1 h.

[0056] The electrolyte-negative electrode integrated structures prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were respectively assembled into batteries, and the assembly process was as follows: The electrolyte-negative electrode integrated structures prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were respectively cut into discs with a diameter of 16 mm to serve as negative electrodes and solid electrolytes. Commercial six-series (622) ternary positive electrode materials were mixed with conductive agent acetylene black (AB) and binder polyvinylidene fluoride (PVDF) in a ratio of 8:1:1 with a total mass of 1 g. The mixture was added to 0.8 ml of N-methylpyrrolidone (NMP), and the mixture was stirred at a speed of 800 r / min for 2 h to obtain a slurry. Use an automatic coating machine to coat the slurry on the current collector aluminum foil, place it flat on tempered glass and transfer it to a vacuum drying oven at 85°C for 4 hours. After punching out circular electrodes with a diameter of 12 mm, dry them at 105°C in a vacuum drying oven for 4 hours. Place them in a glove box filled with argon atmosphere with a water and oxygen content of less than 0.01 ppm for 4 hours to reduce the moisture adsorbed by the electrodes during the transfer process, and then assemble them into CR2032 button batteries in the glove box.

[0057] After the above battery is assembled, it is aged for 12 hours and charged and discharged at a voltage of 8-4.5V and a current density of 0.5C. The cycle performance diagram is shown in Figure 1 and Figure 2 .

[0058] like Figure 1 As shown, the cycle performance curves of the battery assembled from the electrolyte-negative electrode integrated structure prepared in Example 1 are compared with those prepared in Comparative Examples 1 and 2, respectively. It can be seen that the cycle performance of the battery assembled from the electrolyte-negative electrode integrated structure provided in Example 1 is more superior, indicating that the electrolyte-negative electrode integrated structure provided by the present invention can improve the cycle performance of the battery. Comparing the cycle performance curves of the battery assembled from the electrolyte-negative electrode integrated structure prepared in Example 1 and Example 2, it can be seen that the cycle performance of the battery assembled from the electrolyte-negative electrode integrated structure provided in Example 1 is more superior, indicating that adding PTCDA to the solid electrolyte in combination with the activated negative electrode sheet can improve the cycle performance of the battery. Comparing the cycle performance curves of the battery assembled from the electrolyte-negative electrode integrated structure prepared in Comparative Examples 1 and 2, it can be seen that the cycle performance curve of Comparative Example 1 is better than the cycle performance curve of Comparative Example 2, and it can be seen that adding PTCDA to the solid electrolyte can improve the cycle performance of the battery.

[0059] The batteries assembled with the electrolyte-negative electrode integrated structures prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to cyclic voltammetry tests at a scan rate of 1.0 mV / s. The test data are shown in Table 1.

[0060] Table 1 - High voltage window of batteries assembled from electrolyte-negative electrode integrated structures obtained in Examples 1-5 and Comparative Examples 1-2 By comparing the high voltage window data of the battery assembled with the solid composite electrolyte prepared in Example 1 and Comparative Example 1, it can be seen that using PTCDA to activate the lithium sheet can improve the high voltage window of the battery, indicating that the activated lithium sheet provided by the present invention can enable the battery to operate stably at a higher voltage, and the battery has a higher energy density and power output capacity, which is helpful to improve the energy storage capacity and safety performance of the battery.

[0061] The solid electrolyte was cut into 16 mm discs and equipped with a 2032 button cell of stainless steel / electrolyte / stainless steel structure, and an EIS test was performed on an electrochemical workstation to obtain Rs. The ionic conductivity was calculated by σ=L / RsS (L is the electrolyte thickness, S is the contact area). The ionic conductivity of the battery assembled with the electrolyte-negative electrode integrated structure of Examples 1-5 and Comparative Examples 1-2 was 5.6*10 -4 S / cm, 5.2*10 -4 S / cm, 5.3*10 -4 S / cm, 4.9*10 -4 S / cm, 4.7*10 - 4 S / cm, 1.2*10-4 S / cm, 1.0*10 -4 S / cm. From the test data of ionic conductivity, it can be seen that the solid composite electrolyte provided by the present invention can improve the ionic conductivity of the battery.

[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a lithium metal negative electrode, characterized in that: include: A first lithium salt, PTCDA (3,4,9,10-perylenetetracarboxylic dianhydride) and a first solvent are mixed to prepare a solution A, and the solution A is sprayed on one side of a lithium sheet and then dried; the side of the lithium sheet sprayed with the solution A is the activated surface.

2. The method for preparing a lithium metal negative electrode according to claim 1, characterized in that: The first lithium salt is one or more of LiFSI, LiNO3, and LiPF6; the first solvent is one or more of THF and NMP.

3. The method for preparing a lithium metal negative electrode according to claim 1 or 2, characterized in that: In solution A, the concentration of lithium salt is 0.01-0.03 mol / L; the concentration of PTCDA is 1.1-3.3 g / L; the spraying amount of solution A on the lithium sheet is 2-5 μL / cm 2 .

4. A lithium metal negative electrode, characterized in that Prepared by the preparation method according to any one of claims 1 to 3.

5. An electrolyte-negative electrode integrated structure, characterized in that: It comprises a solid electrolyte and a lithium metal negative electrode prepared by the preparation method according to any one of claims 1 to 3 or a lithium metal negative electrode according to claim 4, wherein the active surface of the lithium sheet is bonded to the solid electrolyte.

6. The method for preparing the electrolyte-negative electrode integrated structure according to claim 5, characterized in that: include: The active surface of the lithium sheet is brought into contact with the solid electrolyte, and the lithium metal negative electrode and the solid electrolyte are pressed together.

7. The method for preparing the electrolyte-negative electrode integrated structure according to claim 6, characterized in that: When preparing the solid electrolyte, the second lithium salt, the polymer, PTCDA and the second solvent are mixed to obtain a solution B, and the solution B is coated on the substrate and dried.

8. The method for preparing the electrolyte-negative electrode integrated structure according to claim 7, characterized in that: The second lithium salt is one or more of LiFSI, LiNO3, and LiPF6; the polymer is one or more of PVDF, PVDF-HFP, and PVDF-CTFE; and the second solvent is any one or two of DMF and THF.

9. The method for preparing the electrolyte-negative electrode integrated structure according to claim 8, characterized in that: In solution B, the concentration of the second lithium salt is 0.3-0.7 mol / L; the concentration of the polymer is 80-130 g / L; the concentration of PTCDA is 0.8-3.9 g / L; when the lithium metal anode and the solid electrolyte are pressed together, the pressure is 5-12 N / cm 2 , the pressing time is 0.5-1.5h.

10. A battery, characterized in that: It comprises the electrolyte-negative electrode integrated structure according to claim 5 or the electrolyte-negative electrode integrated structure prepared by the preparation method according to any one of claims 6-9.

Citation Information

Patent Citations

  • Lithium ion battery solid electrolyte with positive and negative electrode interface modification and preparation method of lithium ion battery solid electrolyte

    CN118412528A

  • Positive electrode-solid electrolyte integrated material and preparation method and application thereof

    CN118763293A